Are snakes and spiders special? Acquisition of negative valence and modified attentional processing by non-fear-relevant animal stimuli - Purkis, H.; Lipp, Ottmar (2009)
Previous research has demonstrated differences in processing between fear-relevant stimuli, such as snakes and spiders, and non-fear-relevant stimuli. The current research examined whether non-fear-relevant animal stimuli, such as dogs, birds and fish, were processed like fear-relevant stimuli following aversive learning. Pictures of a priori fear-relevant animals, snakes and spiders, were evaluated as negative in affective priming and ratings and were preferentially attended to in a visual search task. Pictures of dogs, birds and fish that had been trained as CS+ in an aversive conditioning design were evaluated more negatively and facilitated dot probe detection relative to CS- pictures. The current studies demonstrated that stimuli viewed as positive prior to aversive learning were negative and were preferentially attended to after a brief learning episode. We propose that aversive learning may provide a mechanism for the acquisition of stimulus fear relevance.